2006
DOI: 10.1136/thx.2006.064063
|View full text |Cite
|
Sign up to set email alerts
|

Nasal CPAP reduces systemic blood pressure in patients with obstructive sleep apnoea and mild sleepiness

Abstract: Background: A randomised controlled study was undertaken to examine the effect of nasal continuous positive airway pressure (CPAP) on 24 hour systemic blood pressure (BP) in patients with obstructive sleep apnoea (OSA). Methods: Patients were fitted with an ambulatory BP measuring device as outpatients during normal activities and recorded for 24 hours before starting therapeutic or subtherapeutic (4 cm H 2 O) CPAP treatment. BP monitoring was repeated before completion of 12 weeks of treatment. The primary en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 42 publications
1
58
0
Order By: Relevance
“…Altered levels of Bmal1 may contribute to hypertension in SHR through aberrant sleep pattern and changes in the macrostructure of sleep, which have been documented in SHR (39) and Bmal1 Ϫ/Ϫ mice (40), and are similar to disruptions reported in hypertensive patients (41). A causative link between obstructive sleep apnea and hypertension exists in humans (42,43).…”
Section: Discussionmentioning
confidence: 49%
“…Altered levels of Bmal1 may contribute to hypertension in SHR through aberrant sleep pattern and changes in the macrostructure of sleep, which have been documented in SHR (39) and Bmal1 Ϫ/Ϫ mice (40), and are similar to disruptions reported in hypertensive patients (41). A causative link between obstructive sleep apnea and hypertension exists in humans (42,43).…”
Section: Discussionmentioning
confidence: 49%
“…Patients were recruited if they had presented with daytime sleepiness that interfered with daytime function or two of the following symptoms: choking or gasping during sleep, recurrent awakenings from sleep, unrefreshed sleep, daytime fatigue and impaired concentration. 13,14 All subjects underwent a simultaneous sleep study with the portable AL device and in-lab diagnostic PSG (Alice 4; Healthdyne).…”
Section: Methodsmentioning
confidence: 99%
“…14,15 The PSG data were manually scored by an experienced investigator blinded to the clinical data and the results of the AL. Sleep stages were scored according to standard criteria by Rechtschaffen and Kales.…”
Section: Methodsmentioning
confidence: 99%
“…Predefined meta-regression analyses revealed falls of 24-h mean BP by 0.89 per 10 event/h increment in AHI and 1.38 per 1 h/night increment in CPAP use. 83 Three additional randomized controlled trials published after the inclusion period of the meta-analyses were largely confirmatory, [84][85][86] although the study conducted in mostly untreated hypertensive sleepy patients with OSAH showed a substantial and statistically significant reduction in clinic BPs (−6.7/−4.9 mm Hg, systolic/diastolic). 85 The meta-analyses, despite the limitations of the existing trials, suggest that the BP lowering reported with CPAP may not be the only or even the most important beneficial effect on cardiovascular risk of treating OSAH (see section entitled "Effects of treatment of OSAH on cardiovascular diseases and insulin resistance").…”
Section: Effects Of Treatment Of Osah On Htnmentioning
confidence: 97%